(x + 5)(x + 2) = 0
x² + 5x + 2x + 10 = 0
x² + 7x + 10 = 0
- - - - - - -s-
2007-07-05 07:29:44
·
answer #1
·
answered by SAMUEL D 7
·
2⤊
0⤋
USE the FOIL method:
First, Outside, Inside, Last.... sum products ...
X*X + X*2 + 5*X + 5*2
= X^2 + 7X + 10
2007-07-05 14:26:15
·
answer #2
·
answered by Pro bono publico 4
·
0⤊
0⤋
To do this, you use the FOIL method:
F - first
O - outer
I - inner
L - last
Those are the terms that need to be multiplied together to get the final answer:
So, the first terms are x * x = x^2
The outer terms are 2 * x = 2x
The inter terms are 5 * x = 5x
The last terms are 5 * 2 = 10
So, added up you get:
x^2 + 2x + 5x + 10 or
x^2 + 7x + 10
2007-07-05 14:27:29
·
answer #3
·
answered by RG 3
·
0⤊
0⤋
x^2 + 7x+10
2007-07-05 14:24:17
·
answer #4
·
answered by harry 1
·
0⤊
0⤋
(x +5)(x + 2)
x(x+2) +5(x+2)
x^2 +2x+5x+10
x^2 +7x+10
2007-07-05 14:21:50
·
answer #5
·
answered by sweet n simple 5
·
2⤊
2⤋
F.O.I.L
F-first
O-outer
I-Inner
L-last
The first two is x*x=x^2
The outer two is x*2=2x
The inner two is 5*x=5x
The last two is 5*2=10
The answer is x^2+7x+10
2007-07-05 14:30:05
·
answer #6
·
answered by Chiquita S 1
·
0⤊
1⤋